2008
DOI: 10.1080/15257770701845204
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Isothermal Amplification Technologies—A Review

Abstract: Nucleic acid amplification technologies are used in the field of molecular biology and recombinant DNA technologies. These techniques are used as leading methods in detecting and analyzing a small quantity of nucleic acids. The polymerase chain reaction (PCR) is the most widely used method for DNA amplification for detection and identification of infectious diseases, genetic disorders and other research purposes. However, it requires a thermocycling machine to separate two DNA strands and then amplify the requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
301
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(316 citation statements)
references
References 56 publications
1
301
0
14
Order By: Relevance
“…Among these methods, Real Time RT-PCR is the most used and many platforms are available in the routine laboratories (1,2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, Real Time RT-PCR is the most used and many platforms are available in the routine laboratories (1,2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The simple reaction scheme is one of the major advantages of HDA over other methods that often include more than one set of primers and just a singular enzyme [39]. There is no need for an initial denaturation step for DNA and the reaction has the ability to detect RNA [108][109][110][111].…”
Section: E Colimentioning
confidence: 99%
“…This review will discuss different isothermal amplification methods for nucleic acids and their integration into miniaturized systems. Some already published reviews gave a broad overview of that field [36][37][38][39], however, we will have a special view on the most recent strategies to amplify and quantify target molecules in samples. Since the focus of this article is the integration of these technologies into miniaturized systems, the molecular background of the isothermal methods is just briefly described.…”
Section: Introductionmentioning
confidence: 99%
“…However, new PCR technologies, such as isothermal PCR, are of particularly practical use in the diagnosis of enteric fever, as these methods allow for the possibility of developing less-complicated and less-expensive machinery than is necessary for conventional PCR. Several isothermal PCR technologies have been developed (Gill & Ghaemi, 2008), including strand displacement amplification (SDA) (Walker et al, 1992), loop-mediated amplification (LAMP) (Notomi et al, 2000), and helicase-dependent amplification (HDA) (Vincent et al, 2004). Recently, Francois et al have examined the robustness of LAMP for bacterial diagnostic applications using S. Typhi as the target organism (Francois et al, 2011), and demonstrated that LAMP is more sensitive than conventional qPCR and is also a very robust, innovative and powerful molecular diagnostic method.…”
Section: Future Perspectivesmentioning
confidence: 99%